Fifth graders' perceptions of mobile phones and GIS technology - Adiv Gal (Institute of Advanced Engineering and Science, 2019)
The era of M-learning, specifically the use of mobile phones, has been hardly noticeable in elementary schools. GIS technology is also rarely implemented there. In this study, 5th grade students' perceptions of the use of GIS technology through mobile phones were examined as part of an environmental education program designed to help preserve endangered species. The results show that the students provided special, valuable, critical and mature perspectives on the advantages and disadvantages of using mobile phones as part of the innovative pedagogy they apply in school. The use of the mobile phone and the new application as part of M-Learning made it easier for most students to create authentic learning, that is, learning focused on problems in the real world, and included a project of relevance and interest to the learners. The process of learning through mobile phones and GIS technology, which combined the creative use of teaching methods unfamiliar to students, focused on and was adapted to the learners' abilities, offering a diagnosis and constructive guidance based on success and community. In conclusion, 5th grade students testified that their elementary school could enter the M-Learning era by integrating mobile phones and adopting a student-centered learning approach.